Pharmacological applications of Cúrcuma longa L. as medicinal plant: A review (Research, Society and Development, 2020)
Medicinal plants have been widely used in formulations for various therapeutic indications as a prophylactic and activating form of some systems of the organism. One plant that is under increasing study and already has evidences in the literature about its use and effects is the Cúrcuma longa L.. This article presents the main pharmacological activity of Cúrcuma longa L. through a bibliographic research involving articles between 2010 and 2020. The Cúrcuma longa L. in particular its active compound, curcumin, presents several pharmacological applications commonly reported and experienced in vitro by several authors, among them antibacterial activity, antifungal activity, neuroprotective action, anticoagulant, anti-inflammatory. It is concluded that Cúrcuma longa L. is a plant with great possibility of insertion as an adjuvant in the treatment of health problems, from lighter as inflammations to more severe cases as in the pharmacological treatment of cancer. Knowing that plants have a high number of chemicals and that many have already been studied, exploring natural products can show the cure for many diseases. It is therefore expected that such results will contribute to the targeting of new studies on the species in question, guiding research in other areas not yet explored and as well as other compounds extracted from this plant that is promising for the scientific community as a therapeutic alternative.